The reciprocity gap method - Syed Muhammad, Kashif (IIUM Press, 2011)
This chapter discusses reciprocity gap method that makes use of full filed data. In this method, full field displacement data is measured at the specimen boundary. For the case of static loading, displacement-force boundary data is measured and using principle of virtual work, a reciprocity gap functional is reconstructed to give the interior and within the specimen distribution of the elastic tensor. This method has also been applied to the case of finding plate’s flexure rigidities. However, the technique has shown good results for the crack identification problems.